Մի դիմաքանդակի պատմություն - Հասմիկ Պարանյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Статья посвящена одной из важнейших работ жанра портретной скульптуры, являющегося солидной частью творческого наследия великого скульптора XX века Ара Саргсяна, изучению и профессиональному анализу портрета выдающегося археолога, настоящего патриота Тороса Тораманяна. This article is devoted to the study and professional analysis of Toros Toramanyan’s portrait, who is an outstanding architect, archeologist, a true patriot. This work in a bust genre is a significant part of Ara Sargsyan’s creative heritage, a great sculptor of the 20th century.
Keywords: Fine Arts; Sculpture